Perancangan Chassis Prototype Mobil Warak dan Simulasi Statik dengan Metode Finite Element Analysis - Muhammad Yusuf Wibowo; Indra Maulana; Andi Abdullah Ghyferi; Bima Andi Kurniawan; Miftahun Nuril (Politeknik Negeri Jakarta, 2022)
Chassis is the most important part of the vehicle. The purpose of the Chassis is to get optimal results between the size of the Chassis and the level of Safety Factor that is qualified in order to support the needs of the prototype